ANTIFUNGAL PROPHYLAXIS IN IMMUNOCOMPROMISED PATIENTS - Lourdes Vazquez (Mediterranean Journal of Hematology and Infectious Diseases)
Invasive fungal infections (IFIs) represent significant complications in patients with hematological malignancies. Chemoprevention of IFIs may be important in this setting, but most antifungal drugs have demonstrated poor efﬁcacy, particularly in the prevention of invasive aspergillosis. Antifungal prophylaxis in hematological patients is currently regarded as the gold standard in situations with a high risk of infection, such as acute leukemia, myelodysplastic syndromes, and autologous or allogeneic hematopoietic stem cell transplantation. Over the years, various scientific societies have established a series of recommendations for antifungal prophylaxis based on prospective studies performed with different drugs. However, the prescription of each agent must be personalized, adapting its administration to the characteristics of individual patients and taking into account possible interactions with concomitant medication.